Reconstructing worldviews through idioms: Applying cognitive linguistic analysis in teaching Vietnamese as a foreign language - Hang, Nguyen Thi Bich (Edelweiss Applied Science and Technology, 2025)
This article explores the cognitive and cultural foundations of Vietnamese idioms and their pedagogical implications for teaching Vietnamese as a Foreign Language (VFL). Utilizing conceptual metaphor theory, image schemas, and cultural models from cognitive linguistics, the study analyzed a corpus of 100 high-frequency idioms sourced from textbooks and instructional materials. The findings indicate that Vietnamese idioms are systematically motivated by embodied metaphors and culturally shaped worldviews, which reflect values such as the pursuit of emotional depth, expectations of social hierarchy, moral causality, and a cyclical perception of time. While idioms serve as valuable resources for understanding Vietnamese cognition, VFL learners often struggle to interpret them because the conceptual mappings and cultural assumptions embedded within these idioms are unfamiliar. The article proposes a pedagogical model that groups idioms based on their conceptual metaphors, including visual representations and intercultural comparisons. This approach shifts instruction from rote memorization to metaphor-oriented learning, enabling learners to internalize idioms as part of a broader cultural-linguistic system and to develop both linguistic fluency and intercultural understanding.